Healthy Foods North improves diet among Inuit and Inuvialuit women of childbearing age in Arctic Canada. (28th June 2013) - Bains, A.; Pakseresht, M.; Roache, C.; Beck, L.; Sheehy, T.; Gittelsohn, J.; Corriveau, A.; Sharma, S.
Abstract: Background: Healthy Foods North (HFN) is a community‐based intervention designed to promote a healthy diet and lifestyle of Inuit and Inuvialuit populations in Arctic Canada. The objective of the present study was to determine the effects of HFN on the nutrient intake of women of childbearing age. Methods: Six communities in Nunavut ( n  = 3) and the Northwest Territories ( n  = 3) were selected for programme implementation; four received a 12‐month intervention and two served as controls. Quantitative food frequency questionnaires were used to assess dietary intake at baseline and 1 year post‐intervention. Among women participants aged 19–44 years ( n  = 136), 79 were exposed to the intervention and 57 were not. Mean daily energy and nutrient intake and density were determined. Dietary adequacy was assessed by comparing the women's daily nutrient intakes with dietary reference intakes (DRI). Results: Main outcomes were the pre‐ to post‐intervention changes between intervention and control groups for energy and selected nutrient intakes, nutrient density and dietary adequacy. Among the participants, the intervention had a beneficial effect on vitamin A and D intake. The percentage of individuals with nutrient intakes below the DRI increased from pre‐ to post‐intervention for vitamin A and D in the control group but only for vitamin A in the intervention group. The programme did not have a significant impact on calorie, sugar, or fat consumption. Conclusions: The HFN programme is effective in mitigating some of the negative impacts of the nutrition transition on dietary adequacy among Inuit and Inuvialuit women of childbearing age.